Evaluate Right Volunteering Platform for Colgate India Employees - Ghosh, Mehuli (ATLAS SkillTech University, 2024)
The research conducted and recommendations made during an internship at Colgate India for identifying and finalizing suitable volunteering platforms. The objective was to enhance the company's corporate social responsibility (CSR) initiatives by providing employees with effective and meaningful opportunities for community engagement through volunteering. The research focused on various volunteering platforms, considering their features, impact, and alignment with Colgate India's values and objectives.
Project Report on Evaluate Right Volunteering Platform for Colgate India Employees (2022-24) Under the Guidance of Prof. Mehuli Barun Ghosh